Role of Leptin in the Pathogenesis of Reproductive Disorders in Adolescent Girls with Anorexia Nervosa - V. O. Andreyeva (Общая реаниматология, 2007)
Objective: to study a role of leptin in the pathogenesis of reproductive disorders in adolescent girls with anorexia nervosa (AN).Subjects: Two groups of patients the common symptoms of whom were underweight, amenorrhea, the absence of chromosomal or monogenic abnormality. Group 1 consisted of 48 adolescent girls diagnosed as having anorexia nervosa; Group 2 included 41 patients without eating behavioral disorders. A control group comprised 24 patients with a body mass index (BMI) of 20.3 (18.5; 24.9) without eating behavioral disorders and with a normal menstrual cycle. Methods: anthropometry, enzyme immunoassay of plasma leptin and neuropeptide Y levels. The statistical validity of group differences was estimated by the Mann-Whitney U-test.Results. There were reductions in the serum content of leptin in patients at an anorectic stage, its hyperproduction at the stage of AN reduction, and no relationship of the leptin concentration to BMI. Hypoleptinemia at the anorectic stage was accompanied by low neuropeptide Y levels. This suggests that resistance to low leptin levels develops, which may be caused by both impaired leptin transport across the blood-brain barrier and hypoinsulinemia.Conclusion. The low levels of leptin and neuropeptide Y at the anorectic stage may be considered to be an adaptive reaction that delays insulin effects in the presence of malnutrition and creates a vicious circle in the regulation of the lipostat system and vicious circle-associated reproductive disorders.